La vía para revitalizar las condiciones de un planeta vivo o la vía hacía la caída de la vida - Juajibioy, Harold Armando (2025)
This article of reflection based on complex thinking and bibliographic review in dialogue with diverse disciplines and knowledge has the purpose of making the web of life more complex, integrating in a rhizomatic way teleological, cosmogonic, anthropological, sociological, biological, chemical, geological and quantum visions that account for the autopoiesis and the invaluable conditions of a living planet, but also to clarify the presence of a homo sapiens demens creator of an anthropocentric, capitalocentric and global modernity process that breaks the pristine relationship between human beings and nature and provokes poly crises represented by climate change, ecosystem decay, loss of biodiversity, greenhouse gases, lack of vital resources and pollution. In the analytical process based on complex thinking and hermeneutics of text and discourse, the academic and scientific sources were classified into two typologies a) Texts that report on heterogeneous theses on the origin of life and the importance of its care, and b) Texts that are precursors of warning calls on critical points, risk thresholds and threats facing the planet. A total of 31 articles, 42 books and 2 theses were included. The main precautionary conclusion is related to the urgency of retaking a new inter and transdisciplinary reading of the conditions of equilibrium of the planet as a basis for the reinvention of the way of inhabiting.